Pelatihan Pembuatan UML (Unified Modelling Language) Menggunakan Aplikasi Draw.io Pada Prodi Sistem Informasi Universitas Muhammadiyah Jambi - Noneng Marthiawati; Kevin Kurniawansyah; Hafiz Nugraha; Fiqa Khairunnisa (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2024)
Software Modeling is a scientific discipline for studying forms of software modeling that are used as part of the software development stages in a structured and object-oriented manner. This software engineering modeling is presented in Requirements Analysis and described using the Unified Modeling Language (UML) method. UML (Unified Modeling Language) is a visual modeling method used as a means of designing object-oriented systems. UML diagrams that are often used are Use Case Diagrams, Activity Diagrams, Sequence Diagrams, Class Diagrams, Statemachine Diagrams and Component Diagrams. There are several applications that support UML creation, one of which is Draw.io. Draw.io is a website specifically designed for depicting UML diagrams online. It has a very responsive display and is integrated with Google's file storage service, namely Google Drive, so draw.io is an alternative for creating UML diagrams in a shorter time. On this basis, in the Community Service (PkM) program activities on this occasion, UML creation activities were carried out using the draw.io application and assistance in using UML in analyzing needs is one of the right solutions for solving problems in order to expand knowledge, simplify and improve the quality of education. and will overcome problems, time and socio-economic